Legend of the black scorpion - Feng, Xiaogang; Wang, Zhongjun, 1960-; Chong, John.; Sheng, Heyu.; Qiu, Gangjian; Zhang, Ziyi, 1979-; Ge, You, 1957-; Wu, Yanzu, 1974-; Zhou, Xun, 1974-; Ma, Jingwu; Huang, Xiaoming; Tan, Dun, 1957-; et al. ([United States] : Dragon Dynasty ; The Weinstein Company, 2008)
A lavish Chinese epic, set in the Age of Five Dynasties and Ten Kingdoms, tells the story of a royal court in turmoil: forbidden love, deceit, revenge, overpowering beauty, and greed. The second disc contains several in-depth bonus features.
disc 1. Film -- disc 2. Special features.
Special features include optional audio commentary, interviews with director Fen Ziaogang and actor Daniel Wu, and behind-the-scenes and making of segments.
"80991WRP1"--Container.
Screenplay by Sheng Heyu, Qui Gangjian ; director of photography, Zhang Li ; original music, Tan Dun ; piano performance, Lang Lang ; directed by Fen Xiaogang.
Ziyi Zang, Ge You, Daniel Wu, Zhou Xun, Ma Jingwu, Huang Xiaoming.
Not rated.
DVD, region 1; Dolby digital Mandarin 5.1, DTS, English 5.1; widescreen version.
Keywords: Man-woman relationships -- China -- Drama; Deception -- China -- Drama; Revenge -- Drama; Avarice -- Drama; Videorecordings for the hearing impaired; China -- History -- Five dynasties and the Ten kingdoms, 907-979 -- Drama; Epic films; Historical films; Feature films